Carbon Monoxide Preserves Circadian Rhythm to Reduce the Severity of Subarachnoid Hemorrhage in Mice. Issue 9 (September 2017) - Schallner, Nils; Lieberum, Judith-Lisa; Gallo, David; LeBlanc, Robert H.; Fuller, Patrick M.; Hanafy, Khalid A.; Otterbein, Leo E.
Abstract : Background and Purpose—: Subarachnoid hemorrhage (SAH) is associated with a temporal pattern of stroke incidence. We hypothesized that natural oscillations in gene expression controlling circadian rhythm affect the severity of neuronal injury. We moreover predict that heme oxygenase-1 (HO-1/ Hmox1 ) and its product carbon monoxide (CO) contribute to the restoration of rhythm and neuroprotection. Methods—: Murine SAH model was used where blood was injected at various time points of the circadian cycle. Readouts included circadian clock gene expression, locomotor activity, vasospasm, neuroinflammatory markers, and apoptosis. In addition, cerebrospinal fluid and peripheral blood leukocytes from SAH patients and controls were analyzed for clock gene expression. Results—: Significant elevations in the clock genes Per-1, Per-2, and NPAS-2 were observed in the hippocampus, cortex, and suprachiasmatic nucleus in mice subjected to SAH at zeitgeber time (ZT) 12 when compared with ZT2. Clock gene expression amplitude correlated with basal expression of HO-1, which was also significantly greater at ZT12. SAH animals showed a significant reduction in cerebral vasospasm, neuronal apoptosis, and microglial activation at ZT12 compared with ZT2. In animals with myeloid-specific HO-1 deletion ( Lyz-Cre-Hmox1 fl/fl ), Per-1, Per-2, and NPAS-2 expression was reduced in the suprachiasmatic nucleus, which correlated with increased injury. Treatment with low-dose CO rescued Lyz-Cre-Hmox1 fl/fl mice, restored Per-1, Per-2, and NPAS-2 expression, and reduced neuronal apoptosis. Conclusions—: Clock gene expression regulates, in part, the severity of SAH and requires myeloid HO-1 activity to clear the erythrocyte burden and inhibit neuronal apoptosis. Exposure to CO rescues the loss of HO-1 and thus merits further investigation in patients with SAH. Abstract : Supplemental Digital Content is available in the text.